2021
DOI: 10.1558/cj.40926
|View full text |Cite
|
Sign up to set email alerts
|

Integrating and Assessing the Use of a “Makerspace” in a Russian Cultural Studies Course

Abstract: This article discusses the development of an immersive virtual reality (VR)- infused Makerspace for experiential learning. Students in an advanced-level Russian course used a Makerspace to complete a three-part project aimed at language and cultural learning through art and presentational speaking. Participants completed a survey about their experience at the end of the project, thus providing some data by which to assess its success. Students used Oculus Rift headsets to view 360-degree target-culture images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They emphasized the technology's potential in accurately restoring and replicating historical artifacts and architectural elements, offering new methods for conservation. Enkin, E. et al [6] and Berrett, B.E. et al [4] discussed the integration of 3D printing in educational settings, particularly emphasizing project-based learning and reality modeling of campus environments.…”
Section: Literature Workmentioning
confidence: 99%
“…They emphasized the technology's potential in accurately restoring and replicating historical artifacts and architectural elements, offering new methods for conservation. Enkin, E. et al [6] and Berrett, B.E. et al [4] discussed the integration of 3D printing in educational settings, particularly emphasizing project-based learning and reality modeling of campus environments.…”
Section: Literature Workmentioning
confidence: 99%
“…Since it can simulate hi-fidelity engineering experiments in their authentic environments, VR has been used to improve the practical, hands-on learning component in engineering courses. Many subjects, including the sciences (Gupta & Gupta, 2012;Markowitz et al, 2018;Brown et al, 2020), languages (Enkin et al, 2021;Xie et al, 2019), chemistry (Abdinejad et al, 2020;Klingenberg et al, 2020), and mathematics (Cai et al, 2019), have yielded improved learning outcomes among students due to the use of VR.…”
Section: Virtual Reality Technologies In Online Labsmentioning
confidence: 99%
“…Virtual Reality has also been applied in several fields of education, such as linguistics, as an alternative method for teaching languages. Enkin et al (2021) carried out a study in which an effective virtual reality linguistic learning lab was created to teach speaking skills in an advanced-level Russian language course. The findings revealed that utilizing VR to teach Russian increased student motivation, deep learning, focus, and creativity.…”
Section: Virtual Reality Technologies In Online Labsmentioning
confidence: 99%